Comparison of Lactate and Blood Glucose Pre and Post Sub maximal Exercise between Sportswear and Muslim Clothing - Irma Febriyanti, (Arena, 2013)
Abstract Using Muslim clothing for sports on women has been widely used. There is assumption that sports performance with covered Muslim clothing will reduce achievement and speed of fatigue. This research will prove whether such opinion is correct. At the beginning of this study, there are only two indicators studied were lactate and glucose blood. Girls group with open sportswear (K1) compared with the group closed clothes (Muslim clothing: K2) with n each group was 7 people. Both groups are measured lactate and blood glucose before and after exercise (immediately  after physical activity), with a sub maximal load for 5 minutes using Ergocycle. The results showed an increase in body temperature (C o) pre-post-K1: 0.9142 ± 0.260, K2: 1.7285 ± 0.636, a decrease of blood glucose (mg /dl) pre-post; K1 L 15.000 ± 9.933, K2 : 26.857 ± 21.248, an increase in blood lactate (m Mol / l) K1: 6.571 ± 2.537, K2: 6.357 ± 4.940 Changes in blood lactate for open sportswear group (K1) compared with group closed clothes (K2) there was no significant difference p: 0.460. Changes in blood glucose (K1) compared with K2 also no significant difference p: 0.108. Meanwhile, the increase in body temperature by wearing Muslim clothing after physical activity higher than regular sports clothes (p: 0.008). More closed sportswear can be recommended in sports that require a relatively short time.